Enzymatic Modification of Menhaden Oil to Incorporate Caprylic and/or Stearic Acid. (28th May 2019) - Willett, Sarah A.; Martini, Silvana; Akoh, Casimir C.
Abstract: Menhaden oil was enzymatically modified with caprylic (8:0) and/or stearic acid (18:0) to produce structured lipids (SL). The goal was to produce SL with high amounts of polyunsaturated fatty acids (PUFA), a low level of saturation, and a melting point of 25–35 °C. Substrate (menhaden oil to acyl donor) molar ratios were 1:1, 1:3, and 1:5 for 8:0, and 1:1, 1:2, and 1:3 for 18:0. Enzyme load was 10% of the total weight of substrates. Time course study determined optimal time for maximum acyl donor incorporation. Linear interpolation estimated molar ratios that yielded SL with 20 or 30 mol% incorporation of 8:0 or 18:0. Enzymatic reactions were also conducted with molar ratios of menhaden oil to acyl donors:8:0:18:0 (1:1:3, 1:2:2, and 1:3:1). Lipases from Candida antarctica, Lipozyme® 435, and Rhizomucor miehei, Lipozyme® RM IM (Novozymes North America, Inc., Franklinton, NC, USA), were compared for all reactions. Total and sn ‐2 fatty acid compositions, triacylglycerol (TAG) molecular species, thermal behavior, volatile lipid oxidation products, solid fat contents, and oxidative stability were compared. When 8:0 was the acyl donor, the 1:3.03 and 1:4.58 ratios resulted in incorporation of 20 and 30 mol% 8:0, respectively. With 18:0 as the acyl donor, the 1:1.32 and 1:2.41 ratios led to incorporation of 20 and 30 mol% 18:0, respectively. The 1:3:1 ratio SL had a crystallization onset ( C 0 ) of 15.3 °C and a melting completion ( M c ) of 33.1 °C. The physicochemical properties of these SL suggest that some may be useful in formulating food products such as margarines and spreads.